2017
DOI: 10.1038/s41598-017-06592-3
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared femtosecond laser-induced damages in As2S3 and As2Se3 chalcogenide glasses

Abstract: In this paper, we report the first measurements of mid-infrared (MIR) femtosecond laser-induced damage in two typical chalcogenide glasses, As2S3 and As2Se3. Damage mechanism is studied via optical microscopy, scanning electron microscopy and elemental analysis. By irradiating at 3, 4 and 5 μm with 150 fs ultrashort pulses, the evolution of crater features is presented with increasing laser fluence. The dependence of laser damage on the bandgap and wavelength is investigated and finally the laser-induced damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…The maximum refractive index change inside ChG is ∆n = 0.12 and the maximum intensity inside the ChG blocks is 150 GW/cm 2 , as found in the simulation results. The damage threshold of ChG with different compositions measured by the femtosecond laser has been studied by Zhang et al and You et al at the near-infrared and mid-infrared wavelengths, respectively [39,40]. Due to the short pulse duration (100 fs) and a low repetition rate (1 KHz), the damage threshold of ChGs is much larger than the peak intensity required for our reconfigurable metasurface.…”
Section: Reconfigurable Beam With Oammentioning
confidence: 96%
“…The maximum refractive index change inside ChG is ∆n = 0.12 and the maximum intensity inside the ChG blocks is 150 GW/cm 2 , as found in the simulation results. The damage threshold of ChG with different compositions measured by the femtosecond laser has been studied by Zhang et al and You et al at the near-infrared and mid-infrared wavelengths, respectively [39,40]. Due to the short pulse duration (100 fs) and a low repetition rate (1 KHz), the damage threshold of ChGs is much larger than the peak intensity required for our reconfigurable metasurface.…”
Section: Reconfigurable Beam With Oammentioning
confidence: 96%
“…As for ChG-based SCG, the laser-induced damage threshold (LDT) is important when dumping femtosecond pulse with high peak power into the waveguides. The intensity threshold Ith can be calculated by the following equation [25]:…”
Section: Concept and Waveguide Structurementioning
confidence: 99%
“…However, in the form of glasses, chalcogenides are somewhat notorious for their weak mechanical property. When exposed to the strong laser irradiation, the glasses are usually damaged and the glass surface is “burnt” creating gross craters far bigger than the irradiated spot . One of the solutions to improve such weak mechanical property is to induce the growth of the crystalline grains in the glasses via external energy input, such as heating, ion or laser radiation, and thus create so‐called chalcogenide glass‐ceramics.…”
Section: Introductionmentioning
confidence: 99%
“…When exposed to the strong laser irradiation, the glasses are usually damaged and the glass surface is "burnt" creating gross craters far bigger than the irradiated spot. [5][6][7][8][9] One of the solutions to improve such weak mechanical property is to induce the growth of the crystalline grains in the glasses via external energy input, such as heating, ion or laser radiation, and thus create so-called chalcogenide glass-ceramics. This has been successfully demonstrated that the mechanical hardness can be improved several times once the glass-ceramics are created.…”
Section: Introductionmentioning
confidence: 99%